Endodontic treatment of necrosed primary teeth using two different combinations of antibacterial drugs: An in vivo study - C Pinky; K K Shashibhushan; V V Subbareddy (Wolters Kluwer Medknow Publications, 2011)
Aim: This study was conducted to evaluate clinical and radiographic success of endodontic treatment of infected primary teeth using two combinations of antibacterial drugs consisting of ciprofloxacin, metronidazole, and minocycline in one group and ciprofloxacin, ornidazole, and minocycline in the other group. Materials and Methods: The selected 40 teeth were randomly divided into two groups, viz. groups A and B with 20 teeth in each group. In Group A, antibacterial paste containing ciprofloxacin, metronidazole, and minocycline and in Group B, antibacterial paste containing ciprofloxacin, ornidazole, and minocycline mixed with propylene glycol were used. Medication cavities were filled with antibiotic pastes, depending on the groups followed by Glass Ionomer restorations and stainless steel crown placement. Clinical and radiographic evaluation was carried out at 3, 6, and 12 months intervals. Results: Both the groups showed considerable clinical and radiographic success. There was no statistically significant difference between Group A and B. However, group B showed better results clinically and radiographically compared with group A. Conclusions: Both the antibacterial pastes, i.e., combination of ciprofloxacin, metronidazole, and minocycline and ciprofloxacin, ornidazole, and minocycline mixed with propylene glycol have shown good clinical and radiographic success in treating necrotic primary teeth.